Introduced leaf beetles of the Maritime Provinces, 8: Gastrophysa polygoni Linnaeus (Coleoptera: Chrysomelidae) - Lesage, Laurent; Majka, Christopher G. (Zootaxa, 2009)
The taxonomy, nomenclature, identification, introduction history, biology (reproduction, phenology, parasites, predators, host plants), biocontrol potential, susceptibility to pesticides, and economic importance of Gastrophysa polygoni (Linnaeus) in North America are reviewed. This information is part of continuing surveys and research on the adventive leaf beetles of Canada with particular reference to the Maritime Provinces. Known provincial records are confirmed and new locality records are reported for the widely distributed G. polygoni. The introduction timelines and dispersal of the beetle in North America are discussed. Clearly G. polygoni must have been established early in the settlement of North America because reports from the first half of the 19th century already indicated that the species was widely established and common in many locations in the northeastern United States and eastern Canada. Gastrophysa polygoni is beneficial when it feeds on weeds such as Polygonum spp, Fallopia spp, or Rumex spp. It can be a minor pest of cultivated buckwheat (Fagopyrum spp.)